2020
DOI: 10.1002/iub.2375
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SOX2OT/Smad3 feedback loop promotes myocardial fibrosis in heart failure

Abstract: Long noncoding RNA SOX2OT is associated with myocardial fibrosis (MF) in heart failure (HF). This article aims to investigate the role of SOX2OT in MF. We constructed HF mouse models by subcutaneous injection of isoprenaline (ISO). Cardiac fibroblasts (CFs) were treated with ISO to induce MF. Hematoxylin-eosin, Masson, and Sirius-red staining were used to identify myocardial injury and collagen deposition in heart tissues. The relationship among SOX2OT, miR-138-5p, TGF-β1, and Smad3 were evaluated by chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…In recent years, significant progress has been made in the study of lncRNAs regulating cardiac fibrosis (Table 2, Ref. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]). Zhang et al [47] demonstrated that the lncRNA H19 level was significantly downregulated in mice with MI.…”
Section: Lncrnas In Cardiac Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, significant progress has been made in the study of lncRNAs regulating cardiac fibrosis (Table 2, Ref. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]). Zhang et al [47] demonstrated that the lncRNA H19 level was significantly downregulated in mice with MI.…”
Section: Lncrnas In Cardiac Fibrosismentioning
confidence: 99%
“…In recent years, significant progress has been made in the study of lncRNAs regulating cardiac fibrosis (Table 2 , Ref. [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]). Zhang et al .…”
Section: Lncrnas In Cardiac Fibrosismentioning
confidence: 99%
“…SMAD3 is also regulated by serotonin (55) which has been implicated in SUID (56). Variants in this gene have been described in patients that died of sudden cardiac death, heart failure and aortic aneurysm (57)(58)(59)(60)(61).…”
Section: Ros Pathway Variantsmentioning
confidence: 99%
“…SMAD3 is also regulated by serotonin (Chen, 2014) which has been implicated in SUID (Cummings, 2019). Variants in this gene have been described in patients that died of sudden cardiac death, heart failure and aortic aneurysm (Loeys, 2018; Engström, 2020; Ou, 2020; Hanna, 2021; Humeres, 2022).…”
Section: Ros Pathway Variantsmentioning
confidence: 99%
“…In an analysis by Poulet C et al on the potentially abnormal expression of lncRNAs in IPF, lncRNA SOX2OT (SOX2OT) has caught our attention (10). SOX2OT has been confirmed to play a vital part in mesangial cell and cardiomyocyte proliferation and fibrosis in diabetic nephropathy (11,12), suggesting the potentially important effect of SOX2OT on the fibrosis process of IPF. However, no studies have confirmed our view.…”
Section: Introductionmentioning
confidence: 99%